Crime Scene and Distance Correlates of Serial Rape - Warren, E. Janet (Journal of quantitative criminology, 1998)
This study, derived from a sample of 108 serial rapists (rapes=565), examines the relationship between demographic, crime scene, and criminal history variables and the distance traveled by serial rapists in order to offend. The pattern of offenses perpetrated by each of the 108 serial offenders as it relates to his place of residence is also analyzed in terms of known characteristics of the offender and his offenses. The theoretical focus of the study integrates premises derived from criminal investigative analysis, environmental criminology, ethnographic geography, journey to crime research, and criminal geographic targeting to explore the cognitive symmetry between the “how” and the “where” of serial sexual offenses. These components or dimensions of serial crime are explored in an attempt to aid law enforcement in their investigation of hard-to-solve serial crimes.